Effects of Concomitant Schistosoma haematobium Infection on the Serum Cytokine Levels Elicited by Acute Plasmodium falciparum Malaria Infection in Malian Children - Lyke, Kirsten E. (American Society for Microbiology, 2006)
Polyparasitism is common in the developing world, and interactions that alter disease severity may occur. We previously demonstrated that infection with Schistosoma hematobium was associated with protection against Plasmodium falciparum infection in children who were 4 to 8 years old. In this study, we determined whether underlying helminth infections affected the cytokine responses to acute falciparum malaria. A total of 338 schistosomiasis-positive [Sch(+)] children who were 4 to 14 years old were matched by age, residence, and sex with 338 schistosomiasis-negative [Sch(−)] children and monitored for a malaria transmission season (25 weeks). Serologic cytokine levels were measured at the time of the first clinical malaria episode and in children who did not contract malaria. Elevated background levels of interleukin-6 (IL-6) (37.1 pg/ml versus 10.9 pg/ml [P = 0.04]), IL-4 (27.7 pg/ml versus 6.9 pg/ml [P = 0.02]), IL-10 (18.2 pg/ml versus 7.2 pg/ml [P < 0.001]), and gamma interferon (18.2 pg/ml versus 4.7 pg/ml [P = 0.006]) were noted in Sch(+) children compared to Sch(−) children without malaria. IL-6 and IL-10 levels were elevated in association with acute malaria, but the levels appeared to be blunted in Sch(+) children compared to Sch(−) children who were 4 to 8 years old (for IL-6, 96.2 pg/ml versus 137.2 pg/ml [P = 0.08]; for IL-10, 195.9 pg/ml versus 282.2 pg/ml [P = 0.06]). The level of IL-10 was similarly lower in Sch(+) children than in Sch(−) children who were 9 to 14 years old (91.2 pg/ml versus 141.2 pg/ml [P = 0.03]). IL-4 levels were inversely correlated with the time until the first malaria infection in both the Sch(+) children (P < 0.001) and the Sch(−) children (P < 0.001) who were 4 to 8 years old. We postulate that the Th2-enriched environment induced by schistosomiasis protects against malaria and alters the cytokine milieu during an actual infection.